2019
DOI: 10.1111/1365-2664.13323
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture from remote sensing to forecast desert locust presence

Abstract: Preventive control of desert locusts is based on monitoring recession areas to detect outbreaks. Remote sensing has been increasingly used in the preventive control strategy. Soil moisture is a major ecological driver of desert locust populations but is still missing in the current imagery toolkit for preventive management. By means of statistical analyses, combining field observations of locust presence/absence and soil moisture estimates at 1 km resolution from a disaggregation algorithm, we assess the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Le dispositif de prévention a été amélioré ces dernières années à l'aide de nouveaux outils (Cressman, 2008 ;Zhang et al, 2019) comme la télédétection spatiale (Latchininsky et al, 2016). Il est maintenant possible de collecter en temps réel des informations clés sur les conditions écologiques favorables à la reproduction, de les traiter très rapidement et d'envoyer les équipes de prospection dans les zones ayant une forte probabilité d'abriter des populations de criquets pèlerins (Piou et al, 2017(Piou et al, , 2019. Un premier atlas des zones de reproduction (Popov, 1997) a été publié par l'Organisation des Nations Unies pour l'alimentation et l'agriculture (FAO).…”
Section: Introductionunclassified
“…Le dispositif de prévention a été amélioré ces dernières années à l'aide de nouveaux outils (Cressman, 2008 ;Zhang et al, 2019) comme la télédétection spatiale (Latchininsky et al, 2016). Il est maintenant possible de collecter en temps réel des informations clés sur les conditions écologiques favorables à la reproduction, de les traiter très rapidement et d'envoyer les équipes de prospection dans les zones ayant une forte probabilité d'abriter des populations de criquets pèlerins (Piou et al, 2017(Piou et al, , 2019. Un premier atlas des zones de reproduction (Popov, 1997) a été publié par l'Organisation des Nations Unies pour l'alimentation et l'agriculture (FAO).…”
Section: Introductionunclassified
“…The observed accumulation of studies is related to locust outbreaks rather than technological advances and availability of remote sensing data. However, recent analysis related to soil moisture [ 51 , 52 , 53 , 54 ] as well as ecological niche modelling [ 5 , 55 , 56 ] based on several data sources were the focus of investigation and showed promising results.…”
Section: Resultsmentioning
confidence: 99%
“…Using a set of SDMs and climate variables, the authors concluded strong niche conservatism between both subspecies. Piou et al [ 54 ] investigated temporal development for NDVI, soil moisture, rainfall and land surface temperature around survey points of desert locust presence in recession areas. The authors applied statistical analysis for all variables separately to assess their individual potential to explain and forecast desert locust presence.…”
Section: Resultsmentioning
confidence: 99%
“…During the 20th century, research and international cooperation resulted, under the aegis of the Food and Agriculture Organization (Lecoq, 2003), in a concerted management effort based on identifying local hotspots where favourable conditions occur (e.g. Piou et al, 2019), to control potential swarm formation before they transform into a large-scale unmanageable threat (Figure 1a). This approach resulted in a considerable decrease in the number and intensity of locust outbreaks and plagues (Figure 1b).…”
Section: On the Relative Role Of Climate Change And Management In Thementioning
confidence: 99%